Analisis Keberhasilan Proses Pembelajaran Di Lingkungan Kopertis Iii Di Tinjau Dari Rambatan Rata-Rata IPK Mahasiswa Teknik Informatika Angkatan Tahun 2000 / 2001 - Wibisono, Samuel; Ambarwati, Lukita; Hutapea, Sabungan Halomon (JIK: Jurnal Ilmu Komputer, 2008)
Quality control is totally needed in Indonesian education process, beside accreditation as main control, quality control ofÃ‚Â  education grade should be build, with GPA as the indicator by using simple linier regretion method each GPA catagories will be ploted and compared with region ratio. The research done at Kopertis III show that the learning process until eight semester give less differences of GPA, where ideally should be increas every semesterKeywords: Quality of Education, GPA, Ploted of GPA